Можливості впливу на варіанти центральної та периферичної інсулінорезистентності нелікованих раніше хворих із цукровим діабетом 2-го типу - Кіхтяк, О. П. (Clinical Endocrinology and Endocrine Surgery, 2008)
Three month treatment with pioglitazone and metformin showed statistically relevant improvement of the certain list of markers, which depicted central and peripheral insulin resistance. Decreases in glucose, HbA1c, HOMA-index and TNF-α following pioglitazone or metformin were documented. Nadir of fasting insulin level after pioglitazone administration witnesses for acquired thrifty behavior and may also explain increased appetite with subsequent weight gain.